Hypogammaglobulinemia in a child with atypical hemolytic-uremic syndrome - N. S. Zhuravleva; V. I. Kutuzova; M. R. Almerzaeva; N. Yu. Mineeva; O. Yu. Maslov (Медицинская иммунология, 2024)
We present a unique clinical case of an atypical hemolytic-uremic syndrome in a child. The mutation in exon 6 of the CD46 gene (chr1:207940532G>C) leads to a homozygous or hemizygous missense substitution. An 8-year-old girl was urgently hospitalized with symptoms of hemorrhagic syndrome and acute kidney injury. The child from the second pregnancy with an aggravated obstetric anamnesis, the first operative labor at the 38th week, who has an aggravated genealogical anamnesis. Initially, the disease developed in the guise of gastroenterological pathology: the girl had dyspeptic disorders, most likely associated with pathology of carbohydrate metabolism, also frequent infectious diseases and a lag in physical development. From the age of 4 years, the girl suffered from persistent hypoalbuminemia, hypoproteinemia and hypogammaglobulinemia, requiring replacement therapy with intravenous immunoglobulins. She was repeatedly examined in gastroenterological departments in Yekaterinburg and Moscow in 2021-2023, but no data concerning protein-losing enteropathies or primary immunodeficiency was obtained. Also, the whole-exome sequencing with result validation hasn’t confirmed an inherited etiology of the presumed congenital immune error. However, a CD46 gene mutation, associated with the development of hemolytic-uremic syndrome in some publications, was identified in the study. The signs of thrombotic microangiopathy were preceded by fever of unspecified etiology: microangiopathic hemolysis, thrombocytopenia, hyperazotemia, C3 consumption, proteinuria, and macrohematuria; hypercholesterolemia, protein metabolism disorder, increased transaminases, ferritin were also noted. According to the ultrasound of the kidneys there were diffuse changes in the parenchyma, decreased velocity indices of blood flow in both renal arteries at all levels. Differential diagnosis was carried out with thrombotic thrombocytopenic purpura, autoimmune hemolytic anemia, antinuclear form of atypical hemolytic-uremic syndrome, viral and bacterial infections, systemic pathology, antiphospholipid syndrome, and hemoblastosis. The girl didn’t need a renal replacement therapy. When complement-blocking therapy with eculizumab was initiated on vital indications, the signs of the disease were gradually eliminated. The prolonged absence of nephropathy in the child may indicate the diversity of the CD46 gene’s functions and different phenotypic manifestation of its mutations. Analysis of literature sources and detection of CD46 “environment” genes (CYBA, LYST, ARPCIB) by full-exome sequencing suggest ambiguity and polymorphism of phenotypic manifestations of complement-mediated mutation.